Identification of regulatory pathways of miRna and phasiRna related to flax lignan synthesis. Issue 1 (31st December 2023) - Xie, Dongwei; Yang, Xue; He, Ruihua; Ren, Xianghua; Huo, Hang; Yuan, Hongmei; Wu, Guangwen; Su, Jianguang; Sun, Jian
ABSTRACT: Lignan is an important functional health care substance. At present, research on the molecular mechanism of flax lignan biosynthesis is primarily focused at the transcriptional level, with no research on the regulatory mechanism of small RNAs, particularly phased small interfering RNAs (phasiRNAs) related to lignan content. In this study, we used flax seeds at different developmental stages as materials to construct small RNA libraries and degradation libraries. Eighteen known and 4 new miRNA families containing 40 and 4 miRNA members, respectively, were identified. A total of 104 target genes were identified. Using small RNA data for a genome-wide search, a total of twenty-two 21-nt PHAS loci and twenty-eight 24-nt PHAS loci were obtained. Five miRNAs capable of triggering target genes to produce phasiRNAs were identified. These 5 miRNAs triggered their target genes to produce 39 phasiRNAs. Three complete miRNA-PHAS loci-phasiRNA-target gene functional regulatory pathways were identified. Furthermore, qRT‒PCR confirmed an obvious regulatory relationship among the regulatory pathways. In this study, the molecular regulatory network among flax miRNAs, phasiRNAs and target genes was described from the perspective of lignan synthesis, providing an important scientific basis for the study of flax molecular breeding for high lignan content.